Prevalence and associated factors of preeclampsia in two national university hospitals in Cotonou in 2024 - Vodouhe, Tchimon Y. S.; Aboubakar, Moufalilou; Ogoudjobi, Mathieu; Acakpo, Barnard; Hounsa, Chimène; Tshabu Aguemon, Christiane; Denakpo, Justin L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Preeclampsia is one of the direct obstetric complications with a heavy burden, particularly in low- and middle-income countries such as Benin. The objective of this research was to identify the determinants of preeclampsia among pregnant women managed in two national university hospitals in Cotonou in 2024. Methods: The study was conducted in two university hospitals in Cotonou. It was a matched case-control study (two controls for each case), with an analytical aim and prospective data collection from August to October 2024. The threshold for retaining variables in the bivariate analysis was 0.2. Multivariate analysis consisted of a stepwise descending binary logistic regression with a significance level of 0.05. Results: A total of 120 cases of preeclampsia and 240 controls were surveyed. The hospital prevalence of preeclampsia was 11.11%. The mean age was 27.64±6.32 years versus 27.35±5.72 years. Most participants had secondary education (33.33% versus 42.50%) and were nulliparous (45.83% versus 35.42%). The majority of cases were referred (84.17%). Preeclampsia had several determinants: acceptance of the pregnancy by the partner (p=0.013), recent change of partner (p<0.001), existence of stress during pregnancy (p=0.006), nulliparity (p = 0.034), difficult living conditions (p=0.014), place of antenatal care (p<0.001), and multiple pregnancies (p=0.002). Conclusions: Identifying the determinants of preeclampsia will make it possible to target appropriate interventions and preventive measures to reduce its incidence, tailor antenatal care, and improve the maternal and perinatal prognosis of this condition.